Software business : 10th International Conference, ICSOB 2019, Jyväskylä, Finland, November 18-20, 2019, Proceedings /: 10th International Conference, ICSOB 2019, Jyväskylä, Finland, November 18-20, 2019, Proceedings. (2019) - Unknown
No abstract available